1985
DOI: 10.1113/jphysiol.1985.sp015711
|View full text |Cite
|
Sign up to set email alerts
|

Renal extraction and clearance of p‐aminohippurate during saline and dextrose infusion in the rat.

Abstract: SUMMARY1. The reliability of the use of p-aminohippurate (PAH) as a clearance marker for the determination of renal plasma flow during saline or dextrose infusion was investigated in conscious and anaesthetized rats.2. In the conscious rat (wt. 350-400 g) infused for 4 h with 0-85 % saline followed by 3 h of 2-5% dextrose, PAH clearance averaged 11-50 + 1-45 ml/min during saline infusion and 7-83 + 0-82 ml/min during dextrose infusion. The difference was significant (P < 0-02). Inulin clearance, however, was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…probably due to inhibition of PAH secretion by endogenous products accumu lating in the uremic plasma [3,13,15]. Also the renal extraction of PAH has been shown to be decreased by glucose-water infusion [11] and by agents which increase renal blood flow (RBF) [1], Furosemide is an organic anion secreted by the same transtubular transport system as PAH in the proximal tubules [14], However, in previous studies little attention has been given to the possibility that the two sub stances could compete for the same transport system, although several investigations have used PAH clearance to estimate RPF during furosemide diuresis in humans [ 12, 2 1 ]. dogs [9,18,22], and cats [7], Only in one study [18] was RBF measured simultaneously by an electromagnetic flowmeter.…”
Section: Discussionmentioning
confidence: 99%
“…probably due to inhibition of PAH secretion by endogenous products accumu lating in the uremic plasma [3,13,15]. Also the renal extraction of PAH has been shown to be decreased by glucose-water infusion [11] and by agents which increase renal blood flow (RBF) [1], Furosemide is an organic anion secreted by the same transtubular transport system as PAH in the proximal tubules [14], However, in previous studies little attention has been given to the possibility that the two sub stances could compete for the same transport system, although several investigations have used PAH clearance to estimate RPF during furosemide diuresis in humans [ 12, 2 1 ]. dogs [9,18,22], and cats [7], Only in one study [18] was RBF measured simultaneously by an electromagnetic flowmeter.…”
Section: Discussionmentioning
confidence: 99%
“…a fixed value for EpAn close to unity is often used, in order to circumvent the problem with sampling of renal venous blood. However, it has been shown in several studies that EPAH is not a constant pa rameter, but can be influenced by changes in renal blood flow [2], glomerular filtration rate [7], uremia [11], glucose infusion [9], and ad ministration of anionic drugs like furosemide [4], In an earlier study in conscious rats [13] we found that high doses of furosemide markedly decreased EPAH and CPAH. while the corre sponding values for tetraethylammonium (TEA), a compound transported by the orga nic cation system, were relatively unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were performed in anesthetized rats under normal 'control' conditions as well as during infusion of glucose, a condition known to depress EPA H [9]. For this purpose we have applied a newly developed experimental model using an an esthetized rat supplied with an extracorporeal circulation [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has been observed even at low Li concentrations which are similar to plasma levels used in studies where Li is used as a clearance marker for proximal tubular Na transport (0.3 mM). Furthermore, EpAH de-creases during glucose infusion (Lote et al 1985;Rasmussen et al 1990), and during uremia (McNay et al 1976). Changes in RBF (Aukland & Lsyning 1970;Stein et al 1973) and filtration fraction (FF), (Haberle et al 1978) also influences EPAH.…”
Section: ''C-tetraethylammonium As a Marker For Renal Plasma Flow Durmentioning
confidence: 99%